+0  
 
0
148
2
avatar+63 

the function g(x) is defined as g(x) = -2X2 + 3x 

the value fo g(-3) is 

 

 

1) -27

2) -9

3) 27

4) 45

 Nov 14, 2019
 #1
avatar+8873 
+1

g(x)  =  -2x2 + 3x

                                        Replace every  x  with  -3

g(-3)  =  -2(-3)2 + 3(-3)

                                        Evaluate the right side of the equation.

g(-3)  =  -2(9) - 9

 

Can you finish it from here?

 Nov 14, 2019
 #2
avatar+63 
+1

Yes i can thank you very much. 

 Nov 14, 2019

12 Online Users

avatar